U.F.O.S - Brooke, Helen (Oxford University Press, 1999)
Helen Brooke is a contributing author to the Oxford Bookworms Collection. Her book Mystery in London for the the oxford Bookworms Library is a Bestseller. Christine Lindop was born in New Zealand where she began her teaching career. She later taught EFL in France and Spain, and has worked as an editor, proofreader, and writer since 1993.